Writing/translating in/to English: The 'ambivalent' case of Elif Şafak - Akbatur, Arzu. (Thesis (Ph.D.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2010., 2010)
This thesis explores the way Elif Şafak and her work (written and translated in/to English) have been received, represented and de/re-contextualized mainly in the Anglo-American world through a problematization of the discourses formed by the publishers, reviewers, scholars, as well as the writer herself. Apart from this particular Anglo-American context, the Turkish context and Şafak's '(self)translation" into Turkish is also analyzed to foreground the intertwined relationship between the source and target cultures. The thesis sets out to investigate the reception and representation of Şafak and her works from a wider perspective by examining the discourse constructed through the presentation of the books by the publishers, the reviewers' tendencies in recontextualizing and representing the writer and her output, and the writer's utterances in the interviews. The examination of this extratextual discourse is complemented by two case studies; one on the translation of Bit Palas (2002) into English (The Flea Palace, trans. F. Müge Göçek, 2004), the other on The Bastard of Istanbul (2007) originally written in English and then translated into Turkish (Baba ve Piç, 2006) by Aslı Biçen and the author. The critical and descriptive analyses of the case studies explore both the textual discourse formed particularly by Şafak, as revealed in her "writing/translating" strategies and the paratextual discourse emanating from elements such as the cover pages, blurbs, titles, etc. With these two levels of analysis (extratextual and textual), the thesis searches the interaction between translation and/or "self-translation", and the representation of the writer and her work informed by the norms and expectations of the target culture(s). The findings of the study reveal that ġafak's works written/translated in/to English accord with the target culture (principally Anglo-American) norms inscribed with certain linguistic and cultural values, political views as well as stereotypical perceptions of "foreign" cultures. The findings also suggest that the writer as a "selftranslator" played an "interventionist" and trans/formative role in the representation and recontextualization of her work by way of constructing a particular discourse both through her "writing/translating" strategies and her utterances in the interviews.
Keywords: Translating and interpreting.; Turkish fiction -- Translations into English.